Controversies on somatization (Archives of Clinical Psychiatry, 2007)
BACKGROUND: Somatization is frequently found in different health services and it presents controversies in its approaches, diagnoses and referrals to treatment. OBJECTIVES: Making a systematic review on somatization, characterizing how it has been discussed in scientific literature and its indiscriminate use in several clinical settings. We intend to circumscribe the concept and to demonstrate the need of a univocal definition of this classification. METHODS: A literature review was conducted in the Medline and Lilacs databases between the years 2001 and 2004 with the search terms somatization, somatoform disorders and psychosomatic medicine. We proposed a content classification according to the main theme, in association with the concept of somatization, emphasizing questions about classification. RESULTS: We found contradictions in definitions, uses and classifications of somatization. Currently most papers on somatization are connected to psychiatry (191), followed by other medical specialties (139), detecting the spreading out of the concept in many clinical occasions and settings. CONCLUSIONS: There is increasing need for a better understanding of this very prevalent condition in medical settings, causing high costs to health systems. More studies on classification are necessary in order to solve controversies, to simplify the diagnostic process and to improve the somatization approach by health professionals.